Characterization of Brazilian accessions of wild Arachis species of section Arachis (Fabaceae) using heterochromatin detection and fluorescence in situ hybridization (FISH). - Custodio, Adriana Regina (2013)
The cytogenetic characterization of Arachis species is useful for assessing the genomes present in this genus, for establishing the relationship among their representatives and for understanding the variability in the available germplasm. In this study, we used fluorescence in situ hybridization (FISH) to examine the distribution patterns of heterochromatin and rDNA genes in 12 Brazilian accessions of five species of the taxonomic section Arachis. The heterochromatic pattern varied considerably among the species: complements with centromeric bands in all of the chromosomes (A. hoehnei) and complements completely devoid of heterochromatin (A. gregoryi, A. magna) were observed. The number of 45S rDNA loci ranged from two (A. gregoryi) to eight (A. glandulifera), while the number of 5S rDNA loci was more conserved and varied from two (in most species) to four (A. hoehnei). In some species one pair of 5S rDNA loci was observed adjacent to 45S rDNA loci. The chromosomal markers revealed polymorphism in the three species with more than one accession (A. gregoryi, A. magna and A. valida) that were tested. The previous genome assignment for each of the species studied was confirmed, except for A. hoehnei. The intraspecific variability observed here suggests that an exhaustive cytogenetic and taxonomic analysis is still needed for some Arachis species.